Pre and Post Merger Physical Performance of Merged Banks in India - A Select Study - Srinivas, K. (Indian Journal of Finance, 2010)
Over the past few decades, changes in regulation, technological advancement, competitive trends and disintermediation have all led to large scale banking sector consolidation all over the world. Since 1991, the process of Liberalization, Privatization and Globalization initiated by the Government has influenced the functioning and governance of the Indian banking sector.